Fire retardancy of polymers : new strategies and mechanisms - Hull, T. Richard; Kandola, Baljinder K. (Royal Society of Chemistry, 2009)
Globally, fire retardants are needed to satisfy a multibillion dollar market. Fire retardancy of polymeric materials is an important component of fire safety. Fire retardants either reduce the likelihood of ignition and/or reduce the rate of flame spread and hence, escalation of fire. The need to comply with safety legislations forces industry to use fire retardants in materials in order to save lives. With growing consumer demands and new legislations, the development of new systems is an on-going process, which also involves understanding their mechanisms of action. This book covers the late.
Papers arising from: "the 11th Meeting on Fire Retardant Polymers (FRPM'07) which took place in the Albert Halls in Bolton in July 2007"--Page v
Keywords: Fire resistant polymers -- Congresses.; elektronické knihy; electronic books